Conclusions and recommendations - Arkesteijn, Monique (A+BE | Architecture and the Built Environment, 2019)
Even though extensive research into existing CRE alignment models has provided us with valuable insights into the building blocks, components and variables that are needed in the alignment process, these models still fall short in two ways. Most models pay little to no attention to (1) the design of new CRE portfolios and (2) the selection of a new CRE portfolio that adds the most value to the organization. With the development of a new approach, the Preference-based Accommodation Strategy design and decision approach (PAS), I address the deficiencies of the previous alignment models that either place too much emphasis on financial measures or lack clarity in decision making due to the difficulties of quantifying the intangible and subjective. In this chapter the main research question will be answered and recommendations for further research are formulated. How can the Preference-based Accommodation Strategy design and decision approach (PAS) successfully be developed and tested on corporate real estate portfolio level in order to enhance CRE alignment?